FACTORS EFFECTING THE SUCCESS OF SUPPLY CHAIN PARTNERSHIPS –AN EMPIRICAL STUDY ON CHINESE AUTOMOBILE INDUSTRY - Shukri, Shakeerah Mohd; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
This study goals to develop an empirical model to assess the factors that can affect the supply chain partnerships in the industry of automobile in China. The primary data was composed from both suppliers and automobile manufacturers by employing a specially developed questionnaire. The survey was examined using two statistical tools, which are Regression and T – tests. The results showed that the level related to the supply chain technologies usage is still very low. The further improvement of IT infrastructure of supply chain and interaction partnerships should be considered in order to keep the long – term relationship among partners.